OPTIMALISASI BUSINESS MATCHING DI PASAR INTERNASIONAL MELALUI STRATEGI MEDIA SOSIAL DENGAN PENDEKATAN DESIGN THINKING - Pramana, Bujangga Bagus Adi; Setyaningurm, Idfi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The rapid growth of micro, small, and medium enterprises (MSMEs) has motivated the Indonesian government to continuously support them in order to compete in the international market. In line with this, business matching has become one of the government's initiatives aimed at assisting MSMEs in introducing their products through social media, with adaptation to the developments in digitization. PT Wastra Etnik Design is one such MSME in the fashion industry, specializing in the production of Balinese Endek woven fabric, facing challenges in adapting to digitalization, particularly in the development of product marketing. This research aims to provide support to PT Wastra Etnik Design in formulating a business matching strategy through the utilization of social media as a step towards capturing the international market. The research methodology employed is qualitative descriptive research, with primary data collection through interviews and a design thinking approach applied to data analysis. The research findings indicate that the implementation of the design thinking method, with a focus on the development of an e-catalog (digital catalog) in three formats (flipping book or PDF e-catalog, Instagram e-catalog, and Whatsapp Business e-catalog), is considered an optimal and highly effective approach. These e-catalogs assist PT Wastra Etnik Design in better introducing its products and reaching a broader market, thus supporting the goal of MSMEs to compete in the international market.